Pengaruh Budaya Organisasi dan Komitmen Organisasi terhadap Kepuasan Kerja Pegawai Bagian Umum Setda Kota Cimahi - Rahmania, Nia; Sahromi, Sahromi; Saputra, Ginanjar Wira (Jurnal Ilmiah Universitas Batanghari Jambi, 2024)
Every organization can be distinguished from other organizations by a distinctive feature as the identity of the organization. This characteristic is known as organizational culture. Organizational culture is based on correlations that are valued and have norms, ways of behaving and beliefs that characterize individuals or groups that can solve problems. In addition to organizational culture, the authors explained above that there are quality human resources that have an influence on organizational performance, namely organizational commitment. employees who have a commitment to the organization gain the ability to improve performance either individually, in groups or in the organization. This study aims to determine the influence of organizational culture and organizational commitment on employee job satisfaction at the General Section of Regional Secretariat of Cimahi City. The method used in this research is quantitative with a population and sample of all employees at the General Section of Regional Secretariat of Cimahi City with a total of 37 people. The data analysis technique used is simple linear regression analysis. The results obtained in this study F test results obtained calculated F value of 10.134 with a significance of 0.000 <0.006 has a positive value so that it can be said that the pattern of relationship between organizational culture and organizational commitment to employee job satisfaction is unidirectional so that organizational culture and organizational commitment have a relationship significant effect on job satisfaction in the General Section of Cimahi Regional Secretariat.